2003
DOI: 10.1046/j.1526-100x.2003.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting Sedges (Carex spp.) in Southwestern Riparian Meadows

Abstract: The success of revegetation efforts in southwestern U.S. riparian meadows has been limited because natural recolonization is often poor and little is known about establishment of transplanted native meadow species such as sedges. To evaluate their potential use in riparian restoration, the survival and growth of transplanted wildlings of three sedge species, Carex lanuginosa (woolly sedge), C. nebrascensis (Nebraska sedge), and C. rostrata (beaked sedge), were assessed. Transplanting occurred during two season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
0
24
1
1
Order By: Relevance
“…Carex is a globally important genus with more than 2000 species worldwide (Bernard 1990) and has been the focus of restoration research in regions such as temperate North America and the Arctic (e.g., Budelsky and Galatowitsch 2004;Forbes 1993;Galatowitsch and Biederman 1998;Hurd and Shaw 1992;Jones et al 2004;Martin and Chambers 2002;Steed and DeWald 2003;van der Valk et al 1999). In the prairie pothole region of the mid-continental United States, thousands of acres of wetlands have been restored since the mid-1980s, but many native Carex species common to natural prairie pothole wetlands are rare or absent in unplanted restorations, even 12 years after reflooding (Galatowitsch and van der Valk 1996a, c;Mulhouse and Galatowitsch 2003).…”
mentioning
confidence: 99%
“…Carex is a globally important genus with more than 2000 species worldwide (Bernard 1990) and has been the focus of restoration research in regions such as temperate North America and the Arctic (e.g., Budelsky and Galatowitsch 2004;Forbes 1993;Galatowitsch and Biederman 1998;Hurd and Shaw 1992;Jones et al 2004;Martin and Chambers 2002;Steed and DeWald 2003;van der Valk et al 1999). In the prairie pothole region of the mid-continental United States, thousands of acres of wetlands have been restored since the mid-1980s, but many native Carex species common to natural prairie pothole wetlands are rare or absent in unplanted restorations, even 12 years after reflooding (Galatowitsch and van der Valk 1996a, c;Mulhouse and Galatowitsch 2003).…”
mentioning
confidence: 99%
“…We observed the greatest survival from bulrush planted early in the growing season (June) and the greatest mortality from those planted at the end of the growing season (September). Likewise, aquatic Carex (also Cyperaceae) survive best if transplanted early in the growing season (Yetka and Galatowitsch 1999;Steed and DeWald 2003). Sedge shoots grow rapidly in spring due to both the translocation of materials from belowground rhizomes and photosynthesis (Bernard 1975;Bernard and Solsky 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between planting month and rootstock type was the only combination of factors that proved significant for post-winter survival (F = 3.245, P = 0.0214) a primary factor responsible for low survival rates of C. lacustris fall transplants. Steed and DeWald (2003) similarly suggested that the lower belowground reserves of sedges may have been offset by above and below ground plant growth prior to fall that replenished those reserves. Fall transplants have limited carbohydrate, nutrient, and water reserves on which to survive the winter before initiating new growth in spring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are C 3 species of riparian meadows (Winward 1986) and their transpiration rates can be quite high (up to 8.8 mm per day) (Busch 2001). In addition, their survival is related to soil moisture and groundwater depth (Steed and DeWald 2003). Thus, whether native sedges have low rates of water use in urban landscapes needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%